(untitled) (Journal of the College of Basic Education, 2022)
The main target of Viral hepatitis B and C is the liver, the most important organ of lipid and lipoprotein metabolism. Liver inflammation leads to disrupt lipid profile. In this study we investigated the levels of cholesterol, triglycerides, high – density lipoprotein and low – density lipoprotein in sera of 33 HBV patients and 30 HCV patients against 31healthy persons as control group. Correlations between lipids parameters and hepatitis indices (bilirubin total and direct, albumin, alanine transaminase, aspartate transaminase, and alkaline phosphatase) were statistically examined. Cholesterol and low-density lipoprotein found to significantly decreased in both groups of patients while triglycerides decreased in HCV patients. Spearman’s coefficient test revealed significant correlation of triglycerides decrease with bilirubin (total and direct) and albumin increase, high-density lipoprotein decrease with direct bilirubin increase in HBV patients. In HCV patients, cholesterol found to be significantly decrease with alanine transaminase and direct bilirubin increase, triglycerides with direct bilirubin, low-density lipoprotein decrease with aspartate transaminase increase. These results clearly reveal that hepatitis B and C virus patients develop hypolipidemia and its severity positively correlate with hepatitis progression. We suggest that hepatitis B and C patients, especially those in chronic stages, should be examined for the concentrations of serum lipids and maintain their levels at the desired ones to avoid the risk of many disorders associated with these disturbances and, most importantly, to relieve the patients at advanced stages of hepatitis B and C virus infections.